Public holidays in NSW : review of the Banks and Bank Holidays Act 1912 - Riley, Joellen, 1957-; New South Wales. Office of Industrial Relations ([Sydney] : NSW Industrial Relations], 2009)
"On 29 June 2009, the Minister for Industrial Relations, John Hatzistergos endorsed the undertaking of a review to consider the current and future operation of the Banks and Bank Holidays Act 1912. This Act provides for the setting of public holidays in New South Wales. The review has recommended changes to modernise the legislation and other instruments which affect the creation and operation of public holidays and bank holidays."--NSW Industrial Relations website.
Cover title.
"October 2009".
Includes bibliographical references.
Also available online. On 16/12/10 freely available from the website of NSW Industrial Relations at: http://www.industrialrelations.nsw.gov.au/pdfs/Public%20Holidays_Report.pdf
System requirements: Adobe Acrobat Reader to read pdf file.
Keywords: New South Wales; Holidays -- Law and legislation -- New South Wales